Pelatihan Tatacara Sholat bagi Anak-anak di Masjid Jamik Tunggal Bhakti Kelurahan 20 Ilir D I Kecamatan Ilir Timur 1 Palembang - Nurbuana; Sri Safrina; Fitriana; Zaimuddin (Forum Kerjasama Pendidikan Tinggi, 2021)
Prayer is one of the obligatory acts of worship for Muslims. In carrying out prayers, of course, one must know about the conditions, pillars and correct prayer procedures so that prayers do not become in vain. Based on the observations made, there are still children who pray without knowing about the conditions, pillars and correct procedures due to the lack of motivation and knowledge about prayer that they get. Hi, this is the background for carrying out community service regarding prayer procedures for children. The service activities were attended by 30 children consisting of boys and girls. The purpose of this activity is for children to gain knowledge about good and correct prayer procedures, so that later they can practice it in everyday life. The form of this activity is in the form of training that provides added value for the community, especially children, which is delivered through the lecture method, question and answer and demonstration (practice). The results of this community service went well, were successful and received good support in the Jami' Tunggal Bakti Mosque community